(untitled) (Indian Journal of Arid Horticulture, 2015)
The present study was carried out for morphological characterization of thirteen reference varieties of muskmelon (Cucumis melo L.) to validate DUS testing guidelines using plant descriptors adopted from the DUS guidelines of PPV&FRA. Among 34 morphological characteristics studied, 19 were visually assessed and 15 were measured. Under results, no intra-varietal variation was observed for any of the visual characteristics examined. Further, the expression of characters in different varieties remained same for the three consecutive years confirming the uniformity and stability of the variety for visual characteristics. The varieties were grouped into different categories for each character based on 34 descriptors which may be used as reference varieties. The morphological characterization of extant varieties was completed to establish distinctness of the candidate variety from all other varieties to utilize these varieties as reference material for protection of other varieties under PPV&FR Act. A strict maintenance breeding of the reference varieties, including the example varieties, and use of alternate example varieties for conduct of DUS testing in muskmelon, if needed, are also suggested.